Endogenous Viral Elements in Ixodid Tick Genomes - Miranda Barnes; Dana C. Price (Viruses, 2023)
The documentation of endogenous viral elements (EVEs; virus-derived genetic material integrated into the genome of a nonviral host) has offered insights into how arthropods respond to viral infection via RNA interference pathways. Small non-coding RNAs derived from EVE loci serve to direct RNAi pathways in limiting replication and infection from cognate viruses, thus benefiting the host’s fitness and, potentially, vectorial capacity. Here we use informatic approaches to analyze nine available genome sequences of hard ticks (Acari: Ixodidae; Rhipicephalus sanguineus, R. microplus, R. annulatus, Ixodes ricinus, I. persulcatus, I. scapularis, Hyalomma asiaticum, Haemaphysalis longicornis, and Dermacentor silvarum) to identify endogenous viral elements and to illustrate the shared ancestry of all elements identified. Our results highlight a broad diversity of viral taxa as having given rise to 1234 identified EVEs in ticks, with Mononegavirales (specifically Rhabdoviridae) well-represented in this subset of hard ticks. Further investigation revealed extensive adintovirus integrations in several Ixodes species, the prevalence of Bunyavirales EVEs (notably not observed in mosquitoes), and the presence of several elements similar to known emerging human and veterinary pathogens. These results will inform subsequent work on current and past associations with tick species with regard to the viruses from which their “viral fossils” are derived and may serve as a reference for quality control of various tick-omics data that may suffer from misidentification of EVEs as viral genetic material.